Analisis Kemampuan Bioteknologi Farmasi DiTinjau Dari SELF REGULATED LEARNING : Studi Kasus Pada Mahasiswa S1 Farmasi Universitas Mathla’ul Anwar Banten - Firman Rezaldi; Endang Safitri; Nurullah Asep Abdilah; Mu’jijah; Usman Setiawan (Jurnal Biogenerasi, 2022)
This study aims to analyze the ability of students in pharmacy biotechnology courses in terms of student self-regulated learning (high, medium, low). This research is a descriptive research with a qualitative approach. The subjects of this study were all students of the Pharmacy Study Program as many as 30 people consisting of 18 men and 12 women. To obtain data in this study used research instruments consisting of two types, namely test and non-test. The test instrument is a pharmaceutical bitechnology ability test in the form of 10 description questions and a non-test instrument in the form of a self-regulated learning questionnaire. Analysis of pharmaceutical biotechnology capabilities. students were analyzed using a scoring technique and then converted into a value with a range between 0 to 100. The score was then classified into the criteria for minimum completeness. Data analysis of biotechnologist ability. KKM). The results showed that the understanding of pharmaceutical biotechnology was in the high category with an average value of 83.33%.